Respuestas

2014-03-11T13:14:15+01:00

NiCol,
Se trata de la derivada de una división. Aplicamos

 \frac{d}{dx}( \frac{u}{v} ) =  \frac{v\frac{du}{dx}-u\frac{dv}{dx}}{v^{2} }

 \frac{d}{dx}( \frac{2x}{x+1} ) = \frac{(x+1)\frac{d}{dx}(2x)-2x\frac{d}{dx}(x+1)}{(x+1)^{2} }

                                                   =  \frac{(x+1)(2)-2x(1)}{x^{2}+2x+1}

                                                   =  \frac{2x+2-2x}{x^{2}+2x+1}

                                                    \frac{2}{x^{2} +2x+1}